Performance of Employees of the Food Crops and Horticulture Seed Center in Surakarta Region - Sarman; Istiatin; Bambang Mursito (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to examine and analyze the influence of work period, work enthusiasm, level of education, mastery of information technology on employee performance at the Surakarta Region Food Crop and Horticulture Seed Center. This research uses a quantitative research design. The population and sample in this study were 50 employees of the Surakarta Region Food Plant and Horticulture Seed Center. The data analysis technique used for statistical analysis is the multiple linear regression test which is processed using SPSS software. Based on the results of hypothesis testing and discussions that have been carried out, it can be concluded that Years of work, Work Morale, Mastery of Information Technology have a positive and significant influence on Employee Performance. Meanwhile, education level has no effect on employee performance. Keywords :Employee Performance, Years of Work, Work Morale, Education Level, Mastery of Information Technology.